IMPACT OF HELSINKI MOU IMPLEMENTATION INTO THE ACEH GOVERNMENT LAW AS CONFLICT RESOLUTION - Alfian (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This qualitative research presents reflections on conflict and the results of peace in an Aceh region that is included in the unitary state of the Republic of Indonesia The decades-old conflict is an ideological dispute fought by the Free Aceh Movement (GAM) to grow its own autonomous and free state from the Indonesian government. Several parties were initially pessimistic about realizing peace but strengthened again after the 2004 earthquake and tsunami. The Helsinki MoU was not just the result of a long war but due of natural disasters causing the international world to put pressure on the parties so that they finally agreed to make peace. The Government of Indonesia provides a special autonomy legal instrument that is strengthened in the Aceh government law (UUPA) to keep Aceh firmly in a unitary state. The impact of the Helsinki MoU has not been fully on the side of justice in terms of the development of people's welfare. The reality is that political reintegration through local political parties has been able to change the paradigm of GAM fighters to the path of democracy but the local government that exists has not been able to change the situation and change significantly. First, it is believed that the result has not been fully implemented by the UUPA because it is not following the clauses in the Helsinki MoU. Second, some regulations that should be completed by the Indonesian government as a commitment to carrying out peace have not been implemented. This situation could ultimately result in the delegitimization of sustainable peace. This anxiety should be observed so that Aceh as a citizen of the world community can grow and develop well in the future.